An Enduring Path for National Unity and Human Rights Protection in Ethiopia: A Case for Human Dignity Centered Constitutional Design and Interpretation - Gelaye, Tsega Andualem (Mizan law review, 2021)
Ensuring National Unity and upholding Human Rights have always been a big challenge in Ethiopia, since the establishment of the modern Ethiopian state. These problems are still troubling the country, long after the adoption of the present Federal Democratic Republic of Ethiopia (FDRE) Constitution, which is claimed to have addressed them once and for all. This article seeks to revisit the historical underpinnings of the FDRE Constitution and its ethnic-centered design, in relation to its actual capacity to achieve national unity and adequate protection of human rights. The article demonstrates how human dignity centered constitutional design and interpretation could advance both national unity and adequate protection of rights. It argues that the historical foundation of the FDRE Constitution and the design that came out of it is backward looking, exclusionary and inadequate to address both challenges for a number of reasons. As a possible alternative, it proposes a human dignity centered re-reading of history, constitutional design and interpretation. Since Ethiopia is in a process of reform in various spheres, the issues raised and discussed in the article deserve serious attention as they are essential to move forward.